Factors Predicting Childbirth Preparation Information Seeking Behavior among Pregnant Women - Tama, Tanattha; Tachasuksri, Tatirat; Boonnate, Nareerat (NU Journal of Nursing and Health Sciences, 2023)
Childbirth preparation information seeking behavior is significant factor affecting on the ability in childbirth preparation. This study aimed to explore factors predicting childbirth preparation information seeking behavior among pregnant women. The participants were 143 pregnant women who received antenatal care at Queen Savang Vadhana Memorial hospital. Data were collected by self-report questionnaires including demographic data, attitudes towards childbirth, perceived benefits of vaginal birth, subjective norms, information source characteristics, perceived self-efficacy in health information, and childbirth preparation information seeking behavior. Reliabilities of questionnaires were .84, .92, .96, .94, .80 and .85 respectively. Descriptive statistics and multiple regression were used to analyze the data. The result found that an average score of childbirth preparation information seeking behavior was 28.11 (SD = 6.19) The significant predicting factors of childbirth preparation information seeking behavior included information source characteristics (β = .311) and perceived self-efficacy in health information (β = .277). The percentage of total variance explained by these factors among pregnant women was 29.9 (R2= .299) The findings suggested that midwives and other health care providers should improve health resources on childbirth preparation that focus on quality of health information, information access, and several communication channels. In addition, perceived self-efficacy in health information should be promoted for pregnant women.